Struggle for School Equality: The Failures of Desegregating Boston and Milwaukee - Wimmer, Daniel J. (My University, 2017)
This paper examines the school desegregation process that took place in the cities of Milwaukee and Boston. Two common forms of segregation present in these cities since their creation were de facto and de jure. De facto segregation is segregation caused by social norms and ideas, while de jure is segregation using laws. Even though segregated schools were ruled illegal in 1954, many remained segregated into the 1970s through de facto segregation. Throughout the paper I will detail all of the decisions that the two cities school boards made while attempting to complete the court ordered integration. More specifically, I will detail the decisions that ultimately proved to be complete failures. Both Milwaukee and Boston required multiple attempts at integrating the schools, and still weren’t completely successful. My goal is to pinpoint the decisions that the two cities made which caused issues that are still prevalent today. Decisions that these school boards made did not produce much change, and in some cases made the schools throughout the city worse. As well, I hope to find a possible solution that could possibly work in future attempted integration programs.
Series: USGZE AS333
Keywords: African-Americans--Wisconsin--Milwaukee; School integration--Massachusetts--Boston; School integration--Wisconsin--Milwaukee